Response to the Letter to the Editor From Page (2022) Regarding Ellis and Kendall (2021), "Time to Act: Confronting Systemic Racism in Communication Sciences and Disorders Academic Training Programs"...Page, S. J. (2022). Time to RE-act: Ellis and Kendall’s discussion of systemic racism. American Journal of Speech-Language Pathology. Advance online publication - Ellis, Charles; Kendall, Diane (American Journal of Speech-Language Pathology, 2022)
The purpose of this letter is to respond to Page's (2022) letter to the editor, "Time to RE-Act: Ellis and Kendall's Discussion of Systemic Racism," published by the American Journal of Speech-Language Pathology.